Frugivory and seed dispersal in a hyperdiverse plant clade and its role as a keystone resource for the Neotropical fauna - Messeder, Joao Vitor S. (2021)
Background and Aims Much of our understanding of the ecology and evolution of seed dispersal in the Neotropics is founded on studies involving the animal-dispersed, hyperdiverse plant clade Miconia (Melastomataceae). Nonetheless, no formal attempt has been made to establish its relevance as a model system or indeed provide evidence of the role of frugivores as Miconia seed dispersers. Methods We built three Miconia databases (fruit phenology/diaspore traits, fruit-frugivore interactions and effects on seed germination after gut passage) to determine how Miconia fruiting phenology and fruit traits for >350 species interact with and shape patterns of frugivore selection. In addition, we conducted a meta-analysis evaluating the effects of animal gut passage/seed handling on Miconia germination. Key Results Miconia produce numerous small berries that enclose numerous tiny seeds within water- and sugar-rich pulps. In addition, coexisting species provide sequential, year long availability of fruits within communities, with many species producing fruits in periods of resource scarcity. From 2396 pairwise interactions, we identified 646 animal frugivore species in five classes, 22 orders and 60 families, including birds, mammals, reptiles, fish and ants that consume Miconia fruits. Endozoochory is the main dispersal mechanism, but gut passage effects on germination were specific to animal clades; birds, monkeys and ants reduced seed germination percentages, while opossums increased it. Conclusions The sequential fruiting phenologies and wide taxonomic and functional diversity of animal vectors associated with Miconia fruits underscore the likely keystone role that this plant clade plays in the Neotropics. By producing fruits morphologically and chemically accessible to a variety of animals, Miconia species ensure short- and long-distance seed dispersal and constitute reliable resources that sustain entire frugivore assemblages.